Characterization of Cellulose Fibers Extracted from Ulva lactuca with Various NaOH Concentrations - Irianto, Hari Eko; Rachmana, Alfitra Raya; Nurhayati, Nurhayati; Fransiska, Dina; Amanda, Putri; Haryati, Sakinah; Aditia, Rifki Prayoga; Suah, Faiz Bukhari Mohd (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
As demand for sustainable biopolymers is growing, Ulva lactuca has emerged as a promising macroalgal source of cellulose. Alkaline hydrolysis using sodium hydroxide (NaOH) is widely applied in cellulose extraction to remove lignin; however, the influence of NaOH concentration during delignification process of U. lactuca remains insufficiently understood. This study aimed to identify the optimal NaOH concentration for cellulose extraction from U. lactuca and to characterize the resulting fibers. Alkaline treatments were performed using NaOH concentrations of 10%, 20%, 30%, and 40%. The extracted cellulose was evaluated for yield, functional groups, thermal stability, crystallinity index (CrI), and morphology using FTIR, XRD, simultaneous thermal analysis, and FE-SEM. Results showed that cellulose yields ranged from 4.38% to 5.44%, with no significant differences among treatments. In contrast, NaOH concentration significantly affected cellulose morphology, with enhanced delignification and fibrillar refinement observed at higher alkali levels. FTIR spectra confirmed cellulose purity through characteristic O–H and C–H stretching vibrations, β-glycosidic linkages, and the absence of hemicellulose-related peaks. XRD analysis showed that 30% NaOH treatment produced the highest CrI (84.09%), while higher concentrations induced structural degradation. Thermal analysis revealed a two-stage degradation process, consisting of moisture loss at 120–150 °C followed by major cellulose decomposition at 250–300 °C. Overall, 30% NaOH was identified as the optimal concentration for extracting α-cellulose from U. lactuca.